PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DESA SEI TUAN KECAMATAN PANTAI LABU - Lia Teti Siburian; Muhammad Taufik Daniel Hasibuan (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Hypertension is a pressure in the blood vessels exceeding 140 mmHg (systolic) and 90 mmHg (diastolic) on two or more measurements, with an abnormal increase in blood pressure that continues and lasts for more than one period. The American Society of states that hypertension is a progressive cardiovascular syndrome caused by a number of closely related diseases. Objective: To determine the decrease in blood pressure in hypertensive patients before and after music therapy in Sei Tuan Village, Pantai Labu District. Method: This Pre - experimental design research method uses a general research design, but does not use a control group. Pre-experimental design is a design that includes only one group or is given a pre and pos test (The One Group Pretest - Post test). Results: The results of the study conducted on hypertensive patients in Sei Tuan Village showed an increase After the intervention (post-test), there was a significant change in the distribution of blood pressure, a significance value (Asymp. Sig. 2 tailed) of 0.001 was obtained. This value is smaller than the value of α = 0.05 (0.001 <0.05), so it can be concluded that H0 is rejected and Ha is accepted. Conclusion: there is an effect of lowering blood pressure in hypertension sufferers before and after music therapy in Sei Tuan Village, Pantai Labu District. Suggestion: For further researchers, it is hoped that this research will be further developed and the results of the research that has been carried out are expected to be a source of information in increasing insight into non-pharmacological interventions to lower blood pressure in hypertension sufferers.